Analisis Sifat Mekanik Campuran Bubur Kertas Dengan Serat Tanaman Suku Palmae (Arecaceae) - Nazaruddin Yusman; Rakhmad Arief Siregar; Muhammad Yusuf R Siahaan (Agrotekma: Jurnal Agroteknologi dan Ilmu Pertanian, 2021)
To utilize the waste of palm and areca fronds, fiber is used as one of the materials for making composites with a mixture of pulp as the main ingredient. By testing and analyzing the mechanical strength of the material, in order to know the strength of its mechanical properties which can later be potentially applied to cardboard box making materials. Tensile testing was carried out on a composite material mixed with pulp with oil palm and areca nut plant fibers. To carry out the tensile test, a tensile test specimen was made using seven test specimen variables with a composite material of a mixture of pulp with palm midrib and areca nut fibers, with a composition of 30:70, 50:50, and 70:30 in each mixture of each With the addition of one variable specimen of pulp mixed with mixed fiber, namely palm midrib fiber and areca nut with a composition of 30:70. Making specimens using the guidelines on the ASTM 3039M standard. Tensile testing was carried out using a tensile test machine at the Pancasarjana faculty of the University of North Sumatra. The test results were analyzed using the offset method. From the results of the analysis, the highest tensile stress value was found in the specimen, a mixture of pulp and fiber mix composition of 30:70 with a value of 3,058 MPa. The highest fracture strain was found in the mixed pulp specimen with areca nut fiber composition 30:70, with a tensile strain value of 0.0267. The highest yield strength was also found in specimens of mixed pulp with betel nut fiber composition 30:70 with a value of 0.015 MPa. The highest modulus of elasticity was found in the mixed specimen of oil palm midrib fiber at a composition of 30:70 with a value of 1.9107 MPa.